Effects of temperature and nitrogen sources on growth and nitrogen assimilation of Curcuma alismatifolia Gagnep - C. Inkham (2018)
The effects of different temperatures (30/24°C and 30/18°C day/night temperatures) and N sources; nitrate (NO 3-), ammonium (NH 4+), mixed-N source (50 NO 3-:50 NH 4+) in the nutrient solution on growth and N assimilation of Curcuma alismatifolia was studied in a soil-less culture medium. Plant grew taller when grown under the 30/24°C treatment and flower quality in terms of stalk length, size of inflorescence and number of bracts declined at low night temperatures. The highest nitrogen concentration (mg plant -1) in leaves was obtained when plants were supplied with NO 3-as the nitrogen source. Most nitrogen assimilation occurred in leaves at 30/24°C, and in fibrous roots at 30/18°C. There were positive linear relationships between the NO 3- content and NR activity in leaves, when plants were grown under both 30/24°C (R 2= 0.99) and 30/18°C (R 2= 0.96) treatments. The total amino acid concentration in NH 4+-fed plants was significantly higher than that of NO 3--fed plants. Glutamic acid (Glu) was recognized as a major form of accumulated N in old rhizomes, particularly in plants supplied with NO 3-N at 30/18°C, while asparagine (Asn) and aspartic acid (Asp) were the major form of the accumulated N in fibrous roots when plants were cultivated with low night temperature (30/18°C).